2021
DOI: 10.2147/ijgm.s313395
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trend of Urolithiasis Incidence in China: An Age–Period–Cohort Analysis

Abstract: Purpose Urolithiasis is one of the commonest disease of the urinary system. This study aimed to assess the long-term urolithiasis incidence trends in China between 1990 and 2019. Patients and Methods The incidence data of urolithiasis were extracted from Global Burden of Disease Study 2019, and an age–period–cohort framework was used to estimate the age, period, and cohort effects. Results We found that the net drift was −2.72% (95% CI: −2.84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Furthermore, we found as age grew, the risk for urolithiasis presented different trends in the two genders. According to Hui et al., based on data from the Global Burden of Disease Study 2019, for either sex, the urolithiasis incidence in China increased and then decreased with ageing [ 17 ]. Qiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found as age grew, the risk for urolithiasis presented different trends in the two genders. According to Hui et al., based on data from the Global Burden of Disease Study 2019, for either sex, the urolithiasis incidence in China increased and then decreased with ageing [ 17 ]. Qiang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The APC analysis was conducted by arranging incidence, mortality, and population data into consecutive 5-year periods from 1990 to 1994 (median 1992) to 2015–2019 (median 2017) and successive 5-year age intervals from 0–4 years to 90–94 years [ 19 ]. SMM incidence and mortality in patients aged >95 years were not considered in this study since those in this age group are divided into a single group in the GBD database.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the age-standardized incidence rate of urolithiasis among the Chinese population was reported to have been declined from 1990 to 2019, with an annual net drift of −2.7 and −2.1% for men and women, respectively [16 ▪▪ ]. In a cross-sectional study ( n = 2173) conducted in Saudi Arabia, the prevalence of urolithiasis was 11.2% in 2017 [31].…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, in northern Italy, the average age of patients was significantly lower in the 2001–2003 group (45.8 years) than in the 2016–2018 group (57.9 years) [24]. In contrast, several studies in China found that the peak prevalence of urolithiasis was in middle-aged individuals and then decreased with age [14 ▪ ,16 ▪▪ ,33]. Some investigators attributed this to the heavier workload, more occupational stress, less fluid consumption, and thus more dehydration among working individuals [37].…”
Section: Resultsmentioning
confidence: 98%